2022
DOI: 10.1186/s12955-022-01966-2
|View full text |Cite|
|
Sign up to set email alerts
|

Socio-economic correlates of quality of life in single and married urban individuals: a Polish case study

Abstract: Background One of key current social trends is the increasing number of single people. It has multiple implications as single individuals often live and behave differently than those living in relationships. Marital status and socioeconomic status may also be significant quality of life factors for single persons. The aim of this study is to identify relationships between quality of life and selected indicators of socioeconomic status in single and married respondents from the Wrocław metropoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
2
9
0
1
Order By: Relevance
“…Consistent with the World Health Organisation (WHO) social determinants of health framework (36), we hypothesize that a higher socioeconomic status favors a higher quality of life or physical health, mental health, social activities, public health, and vitality (36). Moreover, we recognize that other studies have also correlated socioeconomic status with the quality of life (37,38), indicating that populations with higher social economic status have better quality of life.…”
Section: Discussionmentioning
confidence: 64%
“…Consistent with the World Health Organisation (WHO) social determinants of health framework (36), we hypothesize that a higher socioeconomic status favors a higher quality of life or physical health, mental health, social activities, public health, and vitality (36). Moreover, we recognize that other studies have also correlated socioeconomic status with the quality of life (37,38), indicating that populations with higher social economic status have better quality of life.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, being single was also negatively correlated with lower preferences towards all consultations with healthcare professionals (family doctors, diabetologists, nurses and educators). Contrasted with, on average, lower quality of life and perceived health condition observed among non-married adults in Poland [ 41 ], the attitude of single adults towards preventive health services identified in this study poses a serious challenge.…”
Section: Discussionmentioning
confidence: 67%
“…Table : 3 shows farming experience had a signi cant positive in uence on agrochemical usage. This implies that the more experienced a farmer is the higher he cut down agrochemical usage bearing in mind it advance effect in the environment according to study by (Puciato et al, 2022) who opined reduction the inverse effect of agriculture on the environment by adopting strong and appropriate policies and technological transmission.…”
Section: Effects Of Heavy Metal On Environmental Degradation In the S...mentioning
confidence: 99%
“…Marital status generated a signi cant positive effect on agrochemical usage. This can simply mean married people have been known for a high sense of responsibility and the serious pursuance of means of income that invariably increase their productivity through using more agrochemical to meet their needs (Puciato et al, 2022). Household size signi cantly increased use of agrochemical as well rate of ecological crisis, this simply entails agriculture intensi cation according to FAO (Tilman et al, 2014) who reported Since population is one of the most important determinants of demand, a continuous increase in the world population increases the worldwide demand for food to meet basic human needs (Leonard et al, 2011) a rmed that farmers' family size determines the extent of their involvement in farm operations.…”
Section: Effects Of Heavy Metal On Environmental Degradation In the S...mentioning
confidence: 99%